EFFORTS FOR CHILDREN'S FINE MOTOR DEVELOPMENT THROUGH COLORING SCHEDULE MEDIA IN GROUP B CHILDREN AT TKN PERMATA HATI - Rahma, Rahma; Rizki, Sari (Early Childhood Research Journal (ECRJ), 2022)
The application of the coloring method through drawing sketches in developing children's fine motor skills and being able to find out fine motor development in group B children. The reason for choosing coloring picture sketch media is because coloring is one of the types of activities that children like to increase their creativity and imagination to develop their fine motor skills. This research is a class action research using qualitative data analysis. Data collection methods are carried out by observation and documentation. The instrument used is an observation sheet. The data analysis technique used is descriptive quantitative. Children's attention when learning children's fine motor development activities can be improved through the coloring sketch method. Children's attention has increased each cycle. In the pre-action, the attention of children with good attention criteria was only 40%. After the action in cycle I it increased to 60%, and in Cycle II the child's attention increased again to 93%. so that it can be concluded that the child's response in the activity of coloring a sketch of a picture is able to develop a child's imagination